2015
DOI: 10.3727/096368914x685654
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Tracking and Fate of Intra-Articularly Injected Superparamagnetic Iron Oxide Particle-Labeled Multipotent Stromal Cells in an Ovine Model of Osteoarthritis

Abstract: In this study, superparamagnetic iron oxide (SPIO) particle-labeled mesenchymal stromal cells (MSCs) were injected intra-articularly into osteoarthritic knee joints. Their fate and distribution were evaluated using magnetic resonance imaging (MRI) and macroscopic and histologic postmortem examination. Osteoarthritis was induced in 12 sheep by bilateral meniscectomy. After 6 weeks, one knee joint received 10 × 10(6) SPIO-labeled MSCs (Molday Ion Rhodamine B). Contralateral knees received a control injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 39 publications
(65 reference statements)
1
33
0
Order By: Relevance
“…Interestingly, such local reactions were only observed in horses with severe tendinopathies, regardless of the treatment group; thus, they were not likely to be associated with SPIO-labelling. This is in accordance with previous studies, in which no unwanted side effects of the application of SPIO-labelled cells in vivo were described [ 23 , 26 ]. Furthermore, previous studies showed that no major effects on MSC properties due to SPIO-labelling are to be expected [ 26 , 28 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, such local reactions were only observed in horses with severe tendinopathies, regardless of the treatment group; thus, they were not likely to be associated with SPIO-labelling. This is in accordance with previous studies, in which no unwanted side effects of the application of SPIO-labelled cells in vivo were described [ 23 , 26 ]. Furthermore, previous studies showed that no major effects on MSC properties due to SPIO-labelling are to be expected [ 26 , 28 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a rabbit model of tendon disease, SPIO-labelled MSC could be detected for up to 3 weeks within the tendon by MRI as well as histology [ 26 ]. Moreover, follow-up after intra-articular injection of 10 × 10 6 SPIO-labelled MSC in sheep demonstrated the survival of SPIO-labelled cells for up to 12 weeks by histology [ 23 ]. These results are in contrast to another study using a sheep model of tendon disease, in which SPIO-labelled cells could be detected for up to 7 days only, although hypointense signal caused by free SPIO particles was detected for up to 14 days by MRI [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the above studies, one of the sheep experimental studies has failed to give any positive outcome for the OA conditions compared to the control upon intra-articular implantation of the autologous MSCs. Such observations were recorded using a 0.5 Tesla MRI system after a period of 12 weeks (Delling, Brehm, Metzger, et al 2015). The poor response observed in this study could be due to the weak joint injury induced with meniscal damage that was incapable of inducing discernible osteoarthritic changes in the control group.…”
Section: Msc Studies In Sheepmentioning
confidence: 77%
“…In addition to cultured MSCs, the BM aspirate too has been reported to improve cartilage healing (Duygulu et al 2012). However, no obvious improvement compared to the control was observed in a single study upon use of the BM aspirate (Delling, Brehm, Metzger, et al 2015). MSCs implanted into the joints remain viable and attach themselves to the joint structures Feng et al 2018).…”
Section: Msc Studies In Sheepmentioning
confidence: 99%
“…Furthermore, repair tissue developed in the defect region showed a proteoglycan-and collagen As possible cell source for the repair process MSC from synovial tissue (Hatsushika et al, 2014) or in case of partial meniscectomy meniscus cells itself are conceivable. A study with superparamagnetic iron oxide particle-labeled MSC injected into a sheep joint after medial meniscectomy revealed detectable cells within newly formed "neo-meniscoid" tissue (Delling et al, 2015). Furthermore, migration potential of human meniscus cells has been recently demonstrated in the presence of PRP or human blood serum in vitro (Freymann et al, 2013).…”
Section: Meniscus Tear Repairmentioning
confidence: 99%